2000
DOI: 10.1046/j.1365-2125.2000.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

The xenobiotic inhibitor profile of cytochrome P4502C8

Abstract: Aims To investigate inhibition of recombinant CYP2C8 by: (i) prototypic CYP isoform selective inhibitors (ii) imidazole/triazole antifungal agents (known inhibitors of CYP), and (iii) certain CYP3A substrates (given the apparent overlapping substrate speci®city of CYP2C8 and CYP3A). Methods CYP2C8 and NADPH-cytochrome P450 oxidoreductase were coexpressed in Spodoptera frugiperda (Sf21) cells using the baculovirus expression system. CYP isoform selective inhibitors, imidazole/triazole antifungal agents and CYP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…There have been several reports that CYP3A4 plays a role in the metabolism of CYP2C8 substrates (e.g., cervistatin and paclitaxel) (Sonnichsen et al, 1995;Mück, 1998). What is more, it has been reported that ketoconazole, a potent inhibitor of CYP3A4, inhibits the CYP2C8-catalysed metabolisms of torsemide and paclitaxel (Ong et al, 2000;Bun et al, 2003). These results suggest agents that act as CYP3A4 substrates have the capacity to interact with CYP2C8.…”
Section: Discussionmentioning
confidence: 70%
“…There have been several reports that CYP3A4 plays a role in the metabolism of CYP2C8 substrates (e.g., cervistatin and paclitaxel) (Sonnichsen et al, 1995;Mück, 1998). What is more, it has been reported that ketoconazole, a potent inhibitor of CYP3A4, inhibits the CYP2C8-catalysed metabolisms of torsemide and paclitaxel (Ong et al, 2000;Bun et al, 2003). These results suggest agents that act as CYP3A4 substrates have the capacity to interact with CYP2C8.…”
Section: Discussionmentioning
confidence: 70%
“…CYP3A4 substrates with minor CYP2C8 contribution include carbamazapine (Kerr et al, 1994), verapamil (Tracy et al, 1999), zopiclone (Becquemont et al, 1999), and buprenorphine (Chang et al, 2006). Furthermore, some substrates, such as amiodarone, amitriptyline, quinine, and triazolam, which are metabolized completely or in part by CYP3A, caused Ͼ50% inhibition of CYP2C8 activity at concentrations that corresponded to their CYP3A K m values, suggesting similar affinities for both enzymes (Ong et al, 2000).…”
Section: Human Liver Cyp2c8 Expressionmentioning
confidence: 99%
“…The artemisinin derivatives induce their own elimination, resulting in decreasing concentrations (2), and the hepatic metabolism of artemisinin is mediated in vitro by CYP2B6, as well as by enzymes of the CYP3A subfamily (28). There is evidence for overlapping substrate specificity between CYP2C8 (which is responsible for AQ metabolism) and CYP3A4, an isoform of the CYP3A subfamily (22). Moreover, artemisinin, AQ, and their respective metabolites (DEAQ and dihydroartemisinin) exhibit a range of interactions in vitro (19), and the pharmacokinetics of mefloquine, a quinoline, is altered by concomitant AS administration (16).…”
mentioning
confidence: 99%